Layanan penguasaan konten untuk meningkatkan motivasi belajar siswa - Nurhasanah, Hazna Siti; Susiati, Susiati (Orien: Cakrawala Ilmiah Mahasiswa, 2023)
the aim of this research is to describe and analyze the influence of mind mapping content mastery services on student learning motivation. This research method uses a quantitative approach with a pre-experimental one group pretest-posttest method. The results of this research show that there is an increase in student learning motivation after being provided with mind mapping content mastery services. The pretest results showed that 1 student had a level of learning motivation in the low category, 25 students in the medium category, and 13 students in the high category. Meanwhile, the posttest results showed that there were no students in the low category, 10 students in the medium category, and 29 students in the high category. The results of hypothesis testing through the paired sample t-test obtained a sig value. (2-tailed) is 0.000 ? 0.05, then H0 is rejected and Ha is accepted so it can be concluded that there is an influence of mind mapping content mastery services on student learning motivation.